Paired Reading with parent or volunteer tutors: Do implementation, process features, or tutor characteristics explain differential effects?. (2022) - Villiger, Caroline; Torchetti, Loredana; Hartmann, Erich; Hauri, Silke; Tettenborn, Annette; Näpflin, Catherine; Niggli, Alois
Highlights: Several process features were considered to explain effects of a reading program. None of the five features tested could be confirmed as mediators. Mechanisms of the Paired Reading method are still unexplained. Abstract: Within intervention research, there is still little attention paid to explaining effects. This paper intends to explain differential effects of a Paired Reading study (RCT) of third grade students struggling with reading ( N = 129). The study showed differential effects on reading fluency, depending on whether volunteers or parents conducted the training. The mediating role of several implementation and process features, and the role of tutor characteristics, are investigated. Even though volunteers and parents differed in several aspects regarding implementation, process features and tutor characteristics, these differences cannot explain the differential effects. The difficulty uncovering the components responsible for the efficacy of the method is discussed, and implications for future research presented.